Wpływy z opodatkowania nieruchomości w budżecie dużego miasta w latach 2002-2005 - Kotlińska, Janina (Tax Revenues on Land in the City Budget in the Years Between 2002 and 2005, 2006)
The structure of taxes that the owners of properties in Poland are charged - despite the fact that it has been fourteen years since the local authority has functioned - was changed only twice, that is at the beginning of 1997 and 2003. The last modification was a crucial one. It was an attempt to standardize the method of charging taxes on land in Poland in order to introduce, in the next phase, the so called "cadastre tax". The modifications of the land tax, agriculture tax and forest tax, that have been introduced at the beginning of 2003, can be reflected, to some extent, in the city budget, namely Poznan budget. Nominally, the profit earned on these three types of taxes was increased in 2003 as compared to the previous year, which may be connected to, among other things, other regulation of freedom from these taxes, more severe agriculture tax on land that is not part of a farm or unification of the basis of forest tax. Despite the growth of income from these taxes their share in total revenues of Poznan city, municipality and local income tax have been changed only slightly. Also, the internal structure of revenues on taxes charged on the owners of properties in Poznan was only slightly modified. It does not mean, however, that similar regularity can be found in the budgets of other local governments.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 591-602